Behavior of Mother in Giving Foods to Children in The Kekei, Kiribun, Sokamu, and Kokamu Village of Dekai Subdistrict in Yahukimo District - Martapina Anggai (Health Notions, 2019)
Nutrition is the most important part of a child's growth and development which is related to intelligence and health. Nutritional status of children is influenced by many factors, both directly and indirectly. This study aims to obtain an overview of the behavior of mothers and fulfill the nutritional status of children in Kekei, Kiribun, Kokamu and Sokamu villages in Dekai Subdistrict, Yahukimo District. This study involved mothers of Momuna tribe who had children aged 12 to 60 months in The Kekei, Kiribun, Kokamu, Sokamu village, Yahokimo district, as many as 112 respondents. The sampling technique used multistage random sampling and consecutive sampling. The results of this study showed that 92% of knowledgeable mothers were lacking and 8% were good. Mothers have less attitudes 94% and 6% good. Mothers behave less in fulfilling toddler nutrition 87% and good 13%. The results of this study indicate conditions that are of concern and need continuous handling from both the government, the community and even the local tradition leaders for the recovery of the toddler's nutrition. Keywords: Mother behavior, Feeding, Toddler children